The biodiversity impact of global food value chains Application and evaluation of the first two steps of SBTs for Nature on a Swedish fruit and vegetable wholesaler - Persson, Louise; Vidmark, Wilma (My University, 2024)
With the rate of biodiversity loss higher than any time in history and related up- coming legislative requirements, companies within all sectors must address their impacts and dependencies on biodiversity. One emerging framework for doing so is the Science Based Targets for Nature (SBTs for Nature). The aim of this thesis was to explore how the framework can be applied to a company in the wholesale food sector, in order to assess the biodiversity impacts in the upstream value chain. Further, the thesis aimed to evaluate whether the framework captures the main im- pacts on biodiversity in this context, and identify both challenges and opportunities connected to its application. The wholesale company Ewerman, part of Greenfood Group, was used as a case study, on which the first two steps of the SBTs for Nature were applied by following the technical guidance on SBTs for Nature and gathering both primary and secondary data. A literature study on how agriculture affects bio- diversity was conducted, and its findings compared with the coverage of the SBTs for Nature methodology. Finally, challenges and opportunities were identified from meetings with company representatives, research articles and by reflecting on the work process throughout the project. The application of the framework resulted in rankings of countries according to five pressure categories, based on where estimated pressures, and hence potential im- pacts, are the largest and where nature is the most sensitive. Some countries were frequently ranked high, which provides opportunities for multiple actions within one country. The SBTs for Nature framework captures some aspects of how agriculture affects biodiversity, but overlooks others, most importantly pesticide use. For com- panies within the food sector, the challenges of using the framework are related to the trade-off between accuracy and complexity. Data at a finer scale, and on impacts rather than pressures, would improve the precision of the assessment but can also be resource consuming or even impossible to obtain, at least currently. The framework does however offer opportunities in guiding the direction of companies’ biodiversity strategy, both in terms of where to focus and on what, as well as for complying with regulative requirements such as CSRD and CSDDD. The SBTs for Nature are still under development, and hence needs continuous evaluation as companies within different sectors apply the framework.
Keywords: Biodiversity; Science Based Targets for Nature; Agriculture; Pressure; Impact; Value chain